2017
DOI: 10.1177/0148558x16686740
|View full text |Cite
|
Sign up to set email alerts
|

Clawback Provision of SOX, Financial Misstatements, and CEO Compensation Contracts

Abstract: Section 304 of the Sarbanes-Oxley Act (hereafter, SOX), commonly known as the clawback provision, entitles the Securities and Exchange Commission (SEC) to sue the CEO and CFO in an attempt to recover their incentive compensation based on misstated financial reports. Although a stream of literature investigates the effects of voluntary firm-initiated clawback provisions, this study explores the effects of the mandatory SOX clawback provision on the likelihood of financial misstatements and CEO compensation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…According to DeHaan et al (2013) and , both CEO compensation and PPS were increased by clawback adoption. In contrast, Natarajan and Zheng (2019) found that mandatory SOX clawbacks lead to decreased CEO in-the-money option value. Moreover, clawbacks are linked with decreased asymmetric sensitivity between CEO/CFO cash compensation and firm performance (Liu et al 2019), better sensitivity of unvested (long-term) compensation (Remesal 2018), and higher CFO bonus incentives tied to financial measures (Kroos et al 2018).…”
Section: Consequencesmentioning
confidence: 87%
See 2 more Smart Citations
“…According to DeHaan et al (2013) and , both CEO compensation and PPS were increased by clawback adoption. In contrast, Natarajan and Zheng (2019) found that mandatory SOX clawbacks lead to decreased CEO in-the-money option value. Moreover, clawbacks are linked with decreased asymmetric sensitivity between CEO/CFO cash compensation and firm performance (Liu et al 2019), better sensitivity of unvested (long-term) compensation (Remesal 2018), and higher CFO bonus incentives tied to financial measures (Kroos et al 2018).…”
Section: Consequencesmentioning
confidence: 87%
“…Neoclassical principal agent theory (Ross 1973;Jensen and Meckling 1976;Tirole 1986;Eisenhardt 1989) is the most popular theoretical foundation in clawback research (e.g., Lin 2017;Erkens et al 2018;Liu et al 2020;Natarajan and Zheng 2019). Agency theory focuses on maximizing firm value (Jensen and Meckling 1976) based on the residual claim of principals' stocks and the assumption of homogeneous shareholder preferences (Fama and Jensen 1983).…”
Section: Theoretical and Normative Foundation 21 Principal Agent Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Conyon and He (2016) reported a negative influence of CEO equity-based compensation on fraud. CEO in-the-money-value also reduces restatements, moderated by clawback provisions (Natarajan and Zheng 2019). He (2015) found that CEO inside debt holdings cause decreased restatements.…”
Section: Ceo/cfo Compensationmentioning
confidence: 97%
“…Section 954 of the Dodd-Frank Wall Street Reform and Consumer Protection Act introduces rules requiring firms to further adopt and enforce clawback provisions in 2010. Prior research examines the effect of clawbacks on financial reporting quality, such as earnings management, and on the way executives are compensated (e.g., DeHaan et al 2013;Natarajan and Zheng 2019;Kroos et al 2018).…”
Section: Future Salary Revisionsmentioning
confidence: 99%